Factors Affecting the Utilization of the Elderly Post Integrated Service in the Work Area of Hinai Kiri Health Center, Langkat Regency - Idahman Situmorang; Tri Niswati Utami; Mayang Wulan (Journal La Medihealtico, 2022)
The purpose of the study was to determine the factors that influence the use of posyandu for the elderly in the Hinai Kiri Health Center Work Area, Langkat Regency in 2021. This study uses a quantitative method with a cross sectional design, a population of 1271 people, a sample with a stratified random sampling technique as many as 93 respondents. This study uses a questionnaire. The analysis of this study used univariate, bivariate and multivariate. The statistical test used was the chi square test and logistic regression. The results of the chi-square test were obtained on the knowledge variable p = 0.008, attitude p = 0.005, occupation p = 0.007, distance p = 0.005 and family support p = 0.006 which indicated that there were factors that influenced the use of posyandu for the elderly. The most influential variable is knowledge with an Exp(B) value of 1.438-5.400. The conclusion in this study is that there is an influence of knowledge, attitudes, work, distance and family support on the use of the Posyandu for the elderly in the Hinai Kiri Health Center Work Area, Langkat Regency in 2021. It is recommended to health workers at the Puskesmas in particular to improve counseling and counseling more intensively about the importance of Posyandu the elderly regularly and motivate the elderly to be more routine to participate in elderly visits at least once a month so that the health conditions of the elderly are maintained.